2016
DOI: 10.1080/15287394.2016.1194792
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentrations in fish from three major lakes in north Mississippi: Spatial and temporal differences and human health risk assessment

Abstract: The goal of this study was to compare total mercury (Hg) concentrations in fish muscle tissue and assess consumption health risks of fish collected from three north Mississippi lakes (Sardis, Enid, and Grenada) that are extensively used for fishing and recreation. Largemouth bass (LMB; n = 64), channel catfish (CC; n = 72), and white crappie (WC; n = 100), which represent a range of trophic levels, were collected during spring 2013 and 2014. Creel data estimated that anglers harvested approximately 370,000 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The most common route of human exposure, however, is via the ingestion of food, primarily fish, contaminated with MeHg (Nunes et al 2014; 2014; Wolff et al, 2016; Lopez-Barrera and Barragan-Gonzalez, 2016). The flesh of large predatory fish, such as northern pike, swordfish, shark, and some species of tuna may contain high levels of CH 3 Hg + and represents a major source of Hg exposure (Siedlikowski et al 2016; Burger and Gochfeld 2011).…”
Section: Aging and Exposure To Mercurymentioning
confidence: 99%
“…The most common route of human exposure, however, is via the ingestion of food, primarily fish, contaminated with MeHg (Nunes et al 2014; 2014; Wolff et al, 2016; Lopez-Barrera and Barragan-Gonzalez, 2016). The flesh of large predatory fish, such as northern pike, swordfish, shark, and some species of tuna may contain high levels of CH 3 Hg + and represents a major source of Hg exposure (Siedlikowski et al 2016; Burger and Gochfeld 2011).…”
Section: Aging and Exposure To Mercurymentioning
confidence: 99%
“…The soil in this region is highly erodible, and the erosion rate has been recognized as one of the highest in the nation [23]. This lake has significant natural and recreational resources; however, it is impaired by mercury, and a fish consumption advisory was issued by the Mississippi Department of Environmental Quality (MDEQ) in 1995, which may not be sufficiently protective [24]. In order to reduce the mercury level in the lake, mercury TMDL has been established in the lake watershed [25].…”
Section: Study Sitementioning
confidence: 99%
“…Perez et al (2012) found in Asian community in Philadelphia that although awareness of fish advisories improved, fish consumption remained unchanged. It also needs to be considered that Hg levels in fish may vary significantly among bodies of water across the United States; therefore, published fish advisories may not be appropriate for every location (Wolff et al 2016; Taylor and Williamson 2017).…”
Section: Introductionmentioning
confidence: 99%